Wind farm aerodynamics - Chen, Zheng Hao. (2009)
Wind resource is highly variable both geographically and temporally. Wind power of class 3 or higher is needed for a selected site as wind farm. Physical principles of the conversion of energy, from the extraction of the power of wind to the mechanical power of turbine can be understood from the momentum theory. Betz factor sets the maximum limit of the power coefficient to 0.593. Wake effects can cause energy loss for downwind turbines. The number of turbines that can be arranged on a given site is limited by wake interference, hence seating arrays of wind turbines on a given site is critical for wind farm design. The aim of the project is to perform numerical analysis of wind farm aerodynamics with a focus on the influence of wind turbines interactions in terms of downwind spacing between the wind turbines and wakes interference for maximum power conversions. The optimum configurations for wind turbines to obtain maximum power extractions are proposed.